1999
DOI: 10.1097/00005344-199905000-00018
|View full text |Cite
|
Sign up to set email alerts
|

PPARγ-Ligands Inhibit Migration Mediated by Multiple Chemoattractants in Vascular Smooth Muscle Cells

Abstract: The purpose of this study was to determine the effect of the peroxisome proliferator-activated receptor gamma-(PPAR gamma) ligands troglitazone (TRO), rosiglitazone (RSG), and 15-deoxy-delta prostaglandin J2 (15d-PGJ2) on vascular smooth muscle cell (VSMC) migration directed by multiple chemoattractants. Involvement of mitogen-activated protein kinase (MAPK) in migration also was examined, because TRO was previously shown to inhibit nuclear events stimulated by this pathway during mitogenic signaling in VSMCs.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
112
2
2

Year Published

2000
2000
2010
2010

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 182 publications
(121 citation statements)
references
References 52 publications
4
112
2
2
Order By: Relevance
“…This result suggests the mechanism of action of metformin is not due to an inhibition of intimal hyperplasia but rather to other mechanisms, such as modulation of endothelial function, lipid levels, plasminogen activator inhibitor-1 levels, or platelet reactivity. [5][6][7][8][9][10][11][12][13][14][15][16] We are unable to comment on the potential effects of thiazolidinediones on clinical outcomes compared with nonsensitizer therapy because this medication was not allowed due to potential drug interactions with tranilast. Analysis of our data, excluding insulin-dependent diabetics, showed preserved benefit with respect to MI and a continued trend toward benefit with respect to death (data not shown) in diabetic patients treated with metformin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result suggests the mechanism of action of metformin is not due to an inhibition of intimal hyperplasia but rather to other mechanisms, such as modulation of endothelial function, lipid levels, plasminogen activator inhibitor-1 levels, or platelet reactivity. [5][6][7][8][9][10][11][12][13][14][15][16] We are unable to comment on the potential effects of thiazolidinediones on clinical outcomes compared with nonsensitizer therapy because this medication was not allowed due to potential drug interactions with tranilast. Analysis of our data, excluding insulin-dependent diabetics, showed preserved benefit with respect to MI and a continued trend toward benefit with respect to death (data not shown) in diabetic patients treated with metformin.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] Insulin sensitizers act by decreasing endogenous and exogenous insulin requirements and have other potentially beneficial effects on the cardiovascular system. [5][6][7][8][9][10][11][12][13][14][15][16] We hypothesized that diabetic patients enrolled in the Prevention of Restenosis with Tranilast and its Outcomes (PRESTO) Trial and treated with metformin would demonstrate a lower adverse event rate than diabetic patients treated with non-insulin-sensitizing medications.…”
mentioning
confidence: 99%
“…7,11 In vascular smooth muscle cells and monocytes, activated PPAR␥ inhibits directed migration and targets the expression of matrix metalloproteinases downstream of the extracellular signal-regulated kinases 1 and 2 (ERK 1/2). 12,13 In addition, activated PPAR␥ has a number of other effects in the vasculature, including the modulation of adhesion molecule expression and the regulation of atherogenic and inflammatory processes (for review see Neve et al 14 ).…”
mentioning
confidence: 99%
“…Ang II is known to be a major proatherogenic factor by inducing inflammation in the vessel wall and stimulating proliferation and migration of VSMCs and monocytes. [113][114][115] Previous studies have shown that PPAR-␥ ligands modulate Ang II signaling both at the receptor level and downstream of the Ang II type-1 receptor (AT1-R). PPAR-␥ activators were found to downregulate AT1-R expression in VSMCs and block AT1-R-mediated extracellular signal regulated kinase 1/2 MAPK activation, which is crucial for VSMC proliferation and migration.…”
Section: Inflammation and Atherosclerosismentioning
confidence: 99%